AURAT WANITA: KONSEP DAN HUKUM MENGENAINYA - Ismail, Paizah (Jurnal Syariah, 2019)
This article analyses the concept of aurat applicable to Muslim women in their social life involving non-muhram. Reference has been made to the verses of al-Quran and the prophet traditions as well as the views of the classical Muslim jurists. The finding shows that there are some disagreements between Muslim scholars in some details of application which gives some rooms to everybody or society to apply the teory according to their own situation.